PWE-083 Deranged liver function tests are more indicative of choledocholithiasis in cholecystitis than in patients with gall stone pancreatitis. (22nd June 2015) - Spence, J; Iqbal, F; Donati-Bourne, J; Evans, R; Cheruvu, C; Rao, V
Abstract : Introduction: On table cholangiogram (OTC) is routinely done in patients with deranged liver function tests at the time of laparoscopic cholecystectomy in the setting of acute cholecystitis to rule out choledocholithiasis. However, its role in patients presenting with gall stone pancreatitis is uncertain. Method: A prospective longitudinal cohort study including all consecutive patients who underwent emergency cholecystectomy over a six month period in a busy tertiary centre was undertaken. Demographic data, liver function tests (LFT) and OTC findings of patients who presented with cholecystitis and gall stone pancreatitis were analysed. Differences in levels of bilirubin, alkaline phosphatase and alanine aminotransferase in two subgroups of patients: cholecystitis and gall stone pancreatitis and their relation to presence or absence of choledocholithiasis on OTC was analysed. Statistical analysis was done using Mann-Whitney test. Results: 145 patients (Age: 50; range:16–85, M:F = 44:101) were admitted on an emergency basis over a six month period. 116 patients presented with cholecystitis and 29 patients (20%) had gall stone pancreatitis. Of these 29 patients, 24 (82.8%) had OTC at the time of cholecystectomy. At OTC, 13 (54%) had no stones, while 11 (46%) did have stones. There was no significant difference in levels of bilirubin, alkaline phosphatase and alanine aminotransferase between CBD stone positive and stone negative patients (Bilirubin: 28 v 22; U(df)=59.00, p = 0.49, Alkaline phosphatase: 211 v 145; U(df)=55.00, p = 0.35, Alanine aminotransferase: 273 v 240; U(df)=63.00, p = 0.64; Mann-Whitney test). Of the 116 patients with cholecystitis, 38 (32.8%) had OTC at the time of cholecystectomy. At OTC, 21 (55.3%) had no stones, while 17 (44.7%) did have stones. There was significant difference in levels of bilirubin, alkaline phosphatase and alanine aminotransferase between CBD stone positive and stone negative patients (Bilirubin: 42 v 14; U(df)=34.50, p= <0.0001, Alkaline phosphatase: 275 v 121; U(df)=64.50, p = 0.0009, Alanine aminotransferase: 283 v 50; U(df)=47.50, p = 0.001; Mann-Whitney test). Conclusion: Deranged LFT in a setting of cholecystitis is more predictive of choledocholithiasis as opposed to gall stone pancreatitis. The passage of stone via CBD triggering gall stone pancreatitis may be responsible for deranged LFT rather than retained CBD stones. Hence it is more important to do OTC in patients with cholecystitis and deranged LFT than in patients with gall stone pancreatitis. Disclosure of interest: None Declared.